PENGUATAN KONSEP RASIONALISASI PENGGUNAAN TANAMAN OBAT BERBASIS ETNOMEDISIN MELALUI PELATIHAN DI KEBUN TANAMAN OBAT CITEUREUP - Ibrozi, Hardi Astuti Witasari; Kintoko; Wahyu Titis Lestariningrum (Universitas Ahmad Dahlan, 2024)
Plants as medicine have been a culture since ancient times. The culture of medicine in certain areas (ethnomedicine) has been inherited and preserved. There needs to be a strengthening of the rationality aspect to ensure security. This study aims to measure respondents' knowledge regarding rationalizing the use of ethnomedicine-based medicinal plants, before and after attending the training. This experimental research uses a one-group pretest-posttest design. technique sampling used total sampling, meaning all training participants were used as respondents. Respondents varied greatly. The largest category respondents were aged 51-60, with a bachelor's degree, and worked as entrepreneurs. Knowledge level measurements were carried out before and after training. The intervention was given to respondents through in-class and out-of-class training of 25 hours of learning at the Citeureup Medicinal Plant Garden, Bogor Regency, West Java Province. The mean pretest and posttest scores were 77.69 ± 11.77 and 89.13 ± 4.17 respectively with a significant difference (p <0.05). Therefore, it can be concluded that the 25 hours of training at the Citeureup Medicinal Plant Garden can increase knowledge regarding the concept of rationalizing the use of ethnomedicine-based medicinal plants